2021
DOI: 10.1111/jdv.17700
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk factors for anxiety, depression and post‐traumatic stress disorder through the International Pemphigus and Pemphigoid Foundation

Abstract: The main limitations of our study are its retrospective design and small number of patients. However, it is the largest singlecentre series reported and includes long-term follow-up.SJS/TEN-like CLE has well-defined clinicopathological characteristics and severe cutaneous flares or long-term sequelae should not be expected during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A recent study led by the University of Illinois at Chicago and the International Pemphigus & Pemphigoid Foundation suggested that younger age and systemic corticosteroid therapy are significant predictors for depression and anxiety in pemphigus patients. 23 Other studies have shown controversial results for age and emphasized instea female sex, clinical disease activity in the past, number of days spent as a dermatology inpatient, and shorter clinical remission on the day of assessment. 11,14 In our study, we identified risk factors including autoimmune thyroiditis comorbidity, disease-related hospitalization history, and active mucosal involvement, while age, sex, obesity, disease stage and severity, and corticosteroid use were unexpectedly not associated with anxiety or depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study led by the University of Illinois at Chicago and the International Pemphigus & Pemphigoid Foundation suggested that younger age and systemic corticosteroid therapy are significant predictors for depression and anxiety in pemphigus patients. 23 Other studies have shown controversial results for age and emphasized instea female sex, clinical disease activity in the past, number of days spent as a dermatology inpatient, and shorter clinical remission on the day of assessment. 11,14 In our study, we identified risk factors including autoimmune thyroiditis comorbidity, disease-related hospitalization history, and active mucosal involvement, while age, sex, obesity, disease stage and severity, and corticosteroid use were unexpectedly not associated with anxiety or depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…We further explored the relevant clinicodemographic parameters for mood disorders in pemphigus. A recent study led by the University of Illinois at Chicago and the International Pemphigus & Pemphigoid Foundation suggested that younger age and systemic corticosteroid therapy are significant predictors for depression and anxiety in pemphigus patients 23 . Other studies have shown controversial results for age and emphasized instea female sex, clinical disease activity in the past, number of days spent as a dermatology inpatient, and shorter clinical remission on the day of assessment 11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, continuing evidence has indicated that dry eye is significantly associated with poor quality of life, anxiety, depression, psychiatric symptoms and impaired sleep quality, which also shows a high prevalence in patients with AIBD and leads to serious deleterious effects on quality of life [ 29 , 30 ]. To date, only a few studies have measured subjective well-being in patients with AIBD, and no study has focused on poorer quality of life related to dry eye in patients with AIBD.…”
Section: Discussionmentioning
confidence: 99%
“…The scores are calculated using the following formula: OSDI = (sum of scores for all questions answered × 100)/ (total number of questions answered × 4). Higher scores indicate more severe conditions, and the overall OSDI scores define the ocular surface as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) or severe (above 33) [17].…”
Section: Questionnairesmentioning
confidence: 99%
“…If the autonomic nervous system is affected, it can generate an exacerbated pro-inflammatory response which can be usually encountered in autoimmune diseases [ 96 ]. Several studies have analyzed the impact of autoimmune diseases on quality of life and have concluded that these patients have an affected quality of life, increased stress, depression and anxiety [ 97 , 98 , 99 , 100 , 101 ]. Disease severity can further impact quality of life, as there is a positive correlation with this index [ 102 ].…”
Section: Management Of the Patient With Dg In The Dental Office And N...mentioning
confidence: 99%